Menjinakan Kecemasan Kesehatan Online: Peran Pastoral Konseling Dalam Mengatasi Cyberchondria - Lanongbuka, Amartya Lovelin; Takaendengan, Arni Elsny (PT. Giat Konseling Nusantara, 2024)
Cyberchondria is someone who tends to search excessively for health information on the internet and feels anxious or worried about their health condition based on the information they find. Previous research has provided evidence that health information seeking has a relationship with anxiety, where individuals with higher levels of anxiety will generally browse and search for health information via the internet more often. One of the help services that can be done to overcome the anxiety of cyberchondria sufferers holistically is pastoral counseling services. The purpose of this study is to describe the role of pastoral counseling in overcoming Cyberchondria. The results of this study show that pastoral counseling has an important role in helping individuals overcome anxiety arising from cyberchondria. The pastoral approach offers emotional support, spiritual guidance, and assistance in finding meaning and purpose in life in the context of the health experience by reviewing pastoral functions as supportive, namely guiding, empowering, and reconciling. While pastoral counseling provides important support, more specific treatments such as Cognitive Behavioral Therapy (CBT), psychodynamic therapy, or group therapy may be required from mental health professionals to address cyberchondria in greater depth.